2007
DOI: 10.1164/rccm.200607-941oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cells from Neonates Show a Mesenchymal Stem Cell Phenotype

Abstract: Together, these data demonstrate that tracheal aspirate fluid from premature, mechanically ventilated infants contains fibroblasts with cell markers and differentiation potential typically found in mesenchymal stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 33 publications
8
103
0
Order By: Relevance
“…Finally, we have found that tracheal aspirates from premature infants undergoing mechanical ventilation for respiratory distress express the mesenchymal stem cell markers STRO-1, CD73, CD90, CD105, and CD166, but not hematopoietic and endothelial cell markers. These cells are capable of adipocytic and osteogenic differentiation, and express high levels of a-smooth muscle actin upon TGF-b stimulation (102). Taken together, these results indicate that circulating fibrocytes or mesenchymal stem cells may function as myofibroblast precursors and contribute to the genesis of subepithelial fibrosis in asthma.…”
Section: Airway Smooth Muscle Migrationmentioning
confidence: 73%
“…Finally, we have found that tracheal aspirates from premature infants undergoing mechanical ventilation for respiratory distress express the mesenchymal stem cell markers STRO-1, CD73, CD90, CD105, and CD166, but not hematopoietic and endothelial cell markers. These cells are capable of adipocytic and osteogenic differentiation, and express high levels of a-smooth muscle actin upon TGF-b stimulation (102). Taken together, these results indicate that circulating fibrocytes or mesenchymal stem cells may function as myofibroblast precursors and contribute to the genesis of subepithelial fibrosis in asthma.…”
Section: Airway Smooth Muscle Migrationmentioning
confidence: 73%
“…Hennrick et al 19 reported the presence of MSC found in 11 of 20 endotracheal tube aspirates from ventilated preterm infants with respiratory distress syndrome. In their small study, they noted a trend toward increase days on mechanical ventilation, days of oxygen supplementation and incidence of bronchopulmonary dysplasia in patients from which MSC were isolated and speculated that MSC could be a marker of neonatal lung injury; however, they admit no conclusions can be made without a much larger study powered to evaluate these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our initial outcomes data 9 , we estimated the number of patients needed to find a significant difference in the proportion of infants developing BPD between the MSC and non-MSC groups. Assuming a first group proportion of 0.75, second group proportion of 0.14 and a ratio of sample sizes of 0.81, the sample size calculation to achieve a 90% power for detecting a difference in the proportion of infants developing BPD was 17 in the MSC group and 13 in the no MSC group 13 .…”
Section: Discussionmentioning
confidence: 99%
“…During development, alveolar myofibroblasts are required for the formation of secondary septi 23,24 . Cultured MSCs may also be differentiated to lipofibroblasts 9 , which provide type II cells with neutral lipid for surfactant synthesis 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation